Continuous power generation through a novel solar/geothermal chimney system: Technical/cost analyses and multi-objective particle swarm optimization. (10th February 2021) - Habibollahzade, Ali; Houshfar, Ehsan; Ashjaee, Mehdi; Ekradi, Khalil
Abstract: Consistent power generation using renewable energies has always been a problem, so this study aims to resolve this issue by incorporating a solar/geothermal chimney. Accordingly, a novel hybrid system is proposed to operate on solar and geothermal energies during the day and night time, respectively. Through a parametric study, the proposed system is analyzed from thermodynamic and technoeconomic viewpoints using analytical and CFD simulations to assess the technical aspects and to ensure its practicality. Subsequently, multi-objective particle swarm optimization is applied to the system considering second law efficiency/power output beside levelized electricity cost as the conflicting objectives. The results showed that the proposed system would generate power 24/7, and the power output would be around 3–7 kW for Manzanares solar chimney during the night. With increasing the tower height, the power generation would dramatically increase; the corresponding value can be as high as 300 kW and 50 kW during the day and night for a 350 m tower with a 225 m collector radius. The optimization results show that tower height should be at the maximum studied value regardless of the considered conflicting objectives. The optimization outcomes further indicate that the power output for the geothermal chimney can be as high as 83 kW depending on the operating condition. In addition, the efficiency and levelized electricity cost of the hybrid system can respectively be higher and lower compared to the conventional solar chimney. To sum up, the proposed system can generate power continuously regardless of the meteorological variables e.g. solar radiation and ambient temperature. Highlights: A novel hybrid solar/geothermal chimney is proposed for continuous power generation. Technoeconomic analysis and multi-objective optimization are performed. The tower height should be as high as possible for an improved efficiency. Levelized electricity cost and efficiency directly depend on depth of geothermal pipe. The geothermal chimney can generate up to 83 kW power during the night.